Personal Branding of Politicians through Social Media as Political Communication in Attracting Gen-Z People - Yasa, I Komang Widya Purnama (Persatuan Wartawan Indonesia, 2024)
Personal branding of politicians through social media as political communication in attracting Gen Z people will provide insight into what Gen Z people want with personal branding owned by politicians on social media. The research method uses a descriptive qualitative approach with primary data sources obtained from Mataram City politicians, the General Election Commission and Gen Z people. The location of this research is Mataram City. This research discusses Social Media as Political Communication of Politicians Ahead of the 2024 Election, Personal Branding of Politicians Through Social Media, The Role of Social Media as a Source of Political Information in Increasing Gen Z Support and Gen Z Perception and Response to Political Communication of Politicians. Data obtained from the General Election Commission shows that 18 political parties will compete in the Mataram City area with a total of 534 candidates. The importance of this matter is discussed to provide views to politicians in Mataram City regarding the political communication desired by Gen Z people through social media platforms ahead of the 2024 Election.